Rekonstruksi Kebijakan Hukum Pidana dalam Pemberantasan Mafia Tanah atas Tanah Verponding dan Girik melalui Sistem Pertanahan Elektronik di Indonesia - Meysita Arum Nugroho; Amsori (CV. Era Digital Nusantara, 2026)
Land mafia practices involving verponding and girik land remain a major challenge to legal certainty in Indonesia due to document forgery, overlapping ownership claims, and weaknesses in land administration. Existing criminal law policies primarily rely on general criminal provisions and have not comprehensively addressed the systemic and organized nature of land-related crimes. This study aims to analyze the weaknesses of the current criminal law policy in combating land mafia practices involving verponding and girik land and to formulate a reconstruction model based on the implementation of an electronic land administration system. This research employed a normative legal research method using statutory, conceptual, case, and comparative approaches. Legal materials consisted of primary, secondary, and tertiary legal sources analyzed qualitatively through legal interpretation, legal synchronization, and prescriptive analysis. The findings indicate that the existing criminal law policy remains fragmented and predominantly repressive, while the electronic land administration system offers significant preventive potential through integrated databases, digital audit trails, electronic certificates, and transparent verification mechanisms. However, the effectiveness of electronic land administration depends on institutional integration, cybersecurity, historical validation of land records, and regulatory harmonization. This study proposes a reconstruction of criminal law policy that integrates criminal law enforcement with electronic land administration by strengthening digital evidence, institutional accountability, inter-agency data integration, and preventive legal mechanisms. Such an approach is expected to enhance legal certainty, improve public trust, and provide more effective protection against organized land mafia practices involving verponding and girik land in Indonesia.